Role of community pharmacies in prevention of AIDS among injecting drug misusers: findings of a survey in England and Wales - Glanz, A.; Byrne, C.; Jackson, P. (BMJ, 1989)
OBJECTIVE--To determine the current and potential roles of community pharmacists in the prevention of AIDS among misusers of injected drugs. DESIGN--Cross sectional postal survey of a one in four random sample of registered pharmacies in England and Wales. SETTING--Project conducted in the addiction research unit of the Institute of Psychiatry, London. SUBJECTS--2469 Community pharmacies in the 15 regional health authorities in England and Wales. MAIN OUTCOME MEASURES--Willingness of pharmacists to sell injecting equipment to known or suspected misusers of drugs; pharmacists' attitudes to syringe exchange schemes, keeping a "sharps" box for use by misusers of drugs, and offering face to face advice and leaflets; and opinions of community pharmacists on their role in AIDS prevention and drug misuse. RESULTS--1946 Questionnaires were returned, representing a response rate of 79%. This fell short of the target of one in four pharmacies in each family practitioner committee area in England and Wales, and total numbers of respondents were therefore weighted in inverse proportion to the response rate in each area. The findings disclosed a substantial demand for injecting equipment by drug misusers. After weighting of numbers of respondents an estimated 676 of 2434 pharmacies were currently selling injecting equipment and 65 of 2415 (3%) were participating in local syringe exchange schemes; only 94 of 2410 pharmacies (4%) had a sharps box for used equipment. There was a high degree of concern among pharmacists about particular consequences of drug misusers visiting their premises, along with a widespread acceptance that the community pharmacist had an important part to play. CONCLUSIONS--Promoting the participation of community pharmacists in the prevention of AIDS among misusers of injected drugs is a viable policy, but several problems would need to be overcome before it was implemented.